2017 Brussels Agreement for Latin America: an initiative of the GARD and SLaai - R. Maximiliano Gómez; Sandra Nora González-Díaz; Marilyn Urrutia-Pereira; Marylin Valentín-Rostan; Anahí Yáñez; Edgardo Jares; Álvaro Cruz; Moisés Calderón; Jean Bousquet; Sociedad Latinoamericana de Alergia, Asma; Global Alliance against Chronic Respirat (Revista Alergia México, 2018)
The Global Alliance against Chronic Respiratory Diseases (GARD) is a network of organizations coordinated by the World Health Organization. It is a voluntary alliance of national and international organizations, institutions and agencies with global scope that are committed with actions to improve access to prevention, care and essential medications. On its last annual meeting, celebrated in Brussels (Belgium) in September 2017, the need for actions and representation to be grouped by geographic regions was discussed. There are several successful programs regarding morbidity and mortality control of these diseases, and others that improve cost-benefit and quality of life. Thus, SLaai proposes to contribute to the diffusion and knowledge of chronic respiratory diseases magnitude and risk factors, to identify successful programs in Latin America in order for them to be replicated in the region and to generate strategic alliances for the strengthening of joint actions.